Embodiment and a sense of belonging in online language learning contexts - Intke-Hernandez, Minna (Taikomoji kalbotyra, 2023)
This paper studies how embodiment is realised in distance and online language learning. Eleven students from the University of Helsinki Language Centre participated in the study. The interviews conducted were thematic, and the research question was as follow: How is embodiment evident in students’ narratives about online language learning? I apply nexus analysis (Scollon & Scollon 2004, 2007, 2009) as the analytical method of this study. Focusing on the connections between narratives of historical bodies and language learning in online contexts, four distinct discourses emerged in the data: 1) the lack of embodiment; 2) embodiment as a matter of power; 3) private, safety-giving embodiment; and 4) embodiment in relation to the material and social world.